The World food crisis - Marx, Herbert L. (H. W. Wilson, 1975)
Articles, addresses, and excerpts from books explore the world's food crisis, means of increasing food supply, interrelation between population and food supply, and the role of the United States and United Nations with special reference to the 1974 World Food Conference.